Meningkatkan Minat Belajar Dengan Memanfaatkan Youtube Dan Aplikasi Kumpulan Soal - Bengkel Ginting; Joel Panjaitan (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2022)
Based Program for International Student Assessment ( Bisa) survey, it was released that Indonesia was ranked 72nd out of 77 countries for the student ability category. It is at number 371 for the reading category, and compared to Malaysia which is at number 415. It is at number 379 for mathematics and 396 for science, and compared again with Malaysia, namely at number 440 and 438. Therefore I am motivated to solve problems that arise The problems faced by Rapha'El Simalingkar orphanage children are the lack of interest in learning because they think learning is a boring activity. As well as the target to be achieved, namely increasing interest in learning for the children of the Rapha'El orphanage so that they know how much impact or benefit this learning has. So the solution offered in this field work practice is the provision of motivation and interesting and not boring learning sessions. The Intervention Program used in this Field Work Practice 1 activity is a micro-level intervention (casework) consisting of; Engagement/Intake and Contract, Assessment, Planning, Intervention, Evaluation and Termination.